2002
DOI: 10.1067/mhn.2002.126592
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nitrate Injury in the Rat Sciatic Nerve: A Model of Facial Nerve Injury

Abstract: Functional and neuropathologic data demonstrate that silver nitrate causes significant injury to the rat sciatic nerve. A 5-second cautery causes greater functional impairment and more severe axonal loss than a 1-second injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Microscopic evaluation of axon was performed in a double-blind fashion by three individuals. Each peroneal nerve was graded for damage on a qualitative 4-point scale [19]. Normal nerve received a score of 0 (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Microscopic evaluation of axon was performed in a double-blind fashion by three individuals. Each peroneal nerve was graded for damage on a qualitative 4-point scale [19]. Normal nerve received a score of 0 (Figure 4(a)).…”
Section: Resultsmentioning
confidence: 99%
“…Second, symptoms resulted from acute intoxication with large doses of Ag ϩ include diarrhea, cardiovascular collapse, and convulsions (Dreisbach, 1974), conditions that might be expected to arise from BK channel inhibition (Hagen et al, 2003;Sheehan et al, 2009). Finally, both Ag ϩ treatment and BK channel gene knockout induce neuron degeneration (Wachter et al, 2002;Rü ttiger et al, 2004). Although more work will be required before a clear connection between silver toxicity and irreversible modification of BK channels by Ag ϩ can be made, our results, together with these previous findings, suggest that more attention be paid to the potential cytotoxicity of Ag ϩ .…”
Section: Discussionsupporting
confidence: 50%
“…Neuropathy has also been reported from excessive use of silver sulfadiazine or silver absorption from bone cement (Vik et al, 1985;Payne et al, 1992). In addition, experiments in rats have demonstrated that Ag ϩ causes functional impairment and axonal loss in the sciatic nerve (Wachter et al, 2002) and decreases the volume of the pyramidal cell layer in the developing hippocampus (Rungby et al, 1987). Therefore, it is particularly important to understand the mechanism and molecular targets of Ag ϩ cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The rat sciatic nerve is a similar size to the human facial nerve and has been used extensively as the optimal model for measuring the effects of energy-based devices on the human facial nerve. 11,12 Histologic changes included increased number of mast cells in the perineural soft tissue of 2 nerves dissected by plasma knife. Although the clinical significance of this is unknown, further study will be needed to determine whether stimulation from the plasma knife produces a surrounding inflammatory response.…”
Section: Discussionmentioning
confidence: 99%